Short duration immunochemotherapy followed by radioimmunotherapy consolidation is effective and well tolerated in relapsed follicular lymphoma: 5‐year results from a UK National Cancer Research Institute Lymphoma Group study. (5th February 2016) - Illidge, Tim M.; McKenzie, Hayley S.; Mayes, Sam; Bates, Andrew; Davies, Andrew J.; Pettengell, Ruth; Stanton, Louise; Cozens, Kelly; Hampson, Grace; Dive, Caroline; Zivanovic, Maureen; Tipping, Jill; et al.
Summary: We report a phase II study to evaluate the efficacy and toxicity of abbreviated immunochemotherapy followed by  90 Y Ibritumomab tiuxetan ( 90 Y‐IT) in patients with recurrent follicular lymphoma. Of the 52 patients enrolled, 50 were treated with three cycles of R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) or R‐CVP (rituximab, cyclophosphamide, vincristine, prednisolone), followed by  90 Y‐IT regimen (15 MBq/kg, maximum 1200 MBq) preceded by two infusions of 250 mg/m 2 rituximab. The overall response rate was 98% with complete response (CR) 30% and partial response (PR) 68%. 18 patients with a PR following chemotherapy improved to a CR following  90 Y‐IT: a conversion rate of 40%. Seven patients with PR following  90 Y‐IT subsequently improved to a CR 12–18 months later, leading to an overall CR rate of 44%. With a median follow‐up of 5 years, median progression‐free survival was 23·1 months and overall survival was 77·5% at 5 years. High trough serum rituximab levels (median 112 μg/ml; range 52–241) were attained after four doses of rituximab, prior to  90 Y‐IT; this was not found to influence response rates. The treatment was well tolerated with few (13·5%) grade 3 or 4 infective episodes and manageable haematological toxicity. Abbreviated immunochemotherapy followed by  90 Y‐IT is an effective and well‐tolerated treatment in recurrent follicular lymphoma patients previously exposed to rituximab. Trial registration: clinicaltrials.gov identifier: NCT00637832.